IMPROVING GENERAL AND SPECIAL PHYSICAL FITNESS OF HIGHLY QUALIFIED PARA-ATHLETIC THROWERS (Sciental Journal of Education Humanities and Social Sciences, 2025)
This article highlights priority tasks such as selecting and applying appropriate exercises necessary for training para-athletic throwers, analyzing their body tilt and rotational angles using modern technological tools, and providing methodological resources. It focuses on the growing need for innovative equipment to study, monitor, and optimize the training process of highly qualified para-athletes. Furthermore, it emphasizes the significance of tailoring training loads and the importance of creating specialized conditions to support the sports development of individuals with disabilities.